Retroperitoneal approach in a child with ganglioneuroma: points of technique and literature review - Pietro Impellizzeri; Flora M. Peri; Salvatore Arena; Renato Trimarchi; Carmelo Romeo; Gianlorenzo Dionigi (SpringerOpen, 2022)
Abstract Background data Ganglioneuroma is rare in children and often incidentally discovered. The transperitoneal laparoscopic approach is the surgical choice for most of the surgeons because of the familiar anatomy and the wider working spaces. However, a posterior retroperitoneal approach started to be used in pediatric population demonstrating to be safe and effective. Case presentation We present a case of a child with radiological finding of a right adrenal mass. Due to the increased risk of having a malignant transformation, a surgical resection was decided using a retroperitoneal approach. The adrenal mass was recognized and completely enucleated. The histopathological examination revealed a GN. Clinical course was uneventful with hospital discharge after 3 days. The outcome was evaluated by ultrasound examination performed 3-6 to 12-24 months and then annually. After 24 months, the patient is completely asymptomatic, and no adrenal masses in both sides have been detected. Conclusions The posterior retroperitoneoscopy permits a more direct exposure of the adrenal gland, without violating the peritoneum, and a close vision to the main vessels. We believe that this technique is a valid option for pediatric patients with small adrenal lesions.